Disposal of veterinary supplies used in rural areas from Santa Fe province, Argentina - Tarabla, Pablo Andrés (2023)
The disposal of waste from clinical work may impacts on the environment, animal and public health. Nevertheless, few studies have acknowledged the extent of unproper management of used syringes, needles, medicine containers and other medical supplies in Latinamerica. The objective of this study was to describe means for disposal of veterinary supplies used in rural areas and the factors associated with their discharge in urban areas. A crosssectional study was carried out in 421 veterinarians working with large animals in the province of Santa Fe, Argentina, using a structured questionnaire. Statistical analysis included χ2 and logistic regression. The results showed that less than 50% of the respondents bagged used supplies and a minority did it separately. Potentially hazardous waste was handed out to farm workers for subsequent disposal. Older professionals and those who also worked with small species had, respectively, 1.3 and 1.5 times more risk of discarding in urban areas supplies used on farms. On the contrary, those who had their work residence in the Central Region had a significantly lower probability. Only one in five interviewees had, in their town of residence, availability of accredited transport of hazardous waste. Only 3 to 5% of respondents discarded supplies waste as pathological waste. The close relationship between countryside, towns and cities within the same territory puts public health of urban centers at risk both due to waste disposal and the movement of people from one space to another within the same territory.